Illuminating water cycle modifications and Earth system resilience in the Anthropocene. Issue 4 (31st March 2020) - Gleeson, Tom; Wang‐Erlandsson, Lan; Porkka, Miina; Zipper, Samuel C.; Jaramillo, Fernando; Gerten, Dieter; Fetzer, Ingo; Cornell, Sarah E.; Piemontese, Luigi; Gordon, Line J.; Rockström, Johan; Oki, Taikan; et al.
Abstract: Fresh water—the bloodstream of the biosphere—is at the center of the planetary drama of the Anthropocene. Water fluxes and stores regulate the Earth's climate and are essential for thriving aquatic and terrestrial ecosystems, as well as water, food, and energy security. But the water cycle is also being modified by humans at an unprecedented scale and rate. A holistic understanding of freshwater's role for Earth system resilience and the detection and monitoring of anthropogenic water cycle modifications across scales is urgent, yet existing methods and frameworks are not well suited for this. In this paper we highlight four core Earth system functions of water (hydroclimatic regulation, hydroecological regulation, storage, and transport) and key related processes. Building on systems and resilience theory, we review the evidence of regional‐scale regime shifts and disruptions of the Earth system functions of water. We then propose a framework for detecting, monitoring, and establishing safe limits to water cycle modifications and identify four possible spatially explicit methods for their quantification. In sum, this paper presents an ambitious scientific and policy grand challenge that could substantially improve our understanding of the role of water in the Earth system and cross‐scale management of water cycle modifications that would be a complementary approach to existing water management tools. Plain language summary: Freshwater is crucially important for all life on Earth. There is abundant research and evidence on how different processes within the water cycle regulate climate and support ecosystems, and by extension, human societies. Humans are also a major force disturbing those processes and modifying the water cycle. These modifications include, for instance, surface water withdrawals, groundwater pumping, deforestation and other land cover change, and ice melt due to warming climate. As most previous research on human–water interactions focuses on understanding systems at smaller scales, such as a watershed or a nation, comprehensive understanding of what human modifications of the water cycle mean for the stability of the planet is still lacking. In this paper we propose a new framework for analysing and establishing limits to a variety of human modifications of the water cycle, to ensure that the stability of the Earth would not be compromised. We see this as an important and urgent scientific challenge that has the potential to substantially improve our understanding of the functioning of the Earth system and to inform local and global policy toward a more sustainable future. Key Points: Earth system resilience depends on an improved understanding and management of water cycle modifications We identify four key functions of freshwater in the Earth system and evidence of regional to global regime shifts and disruptions The water planetary boundary is a compelling framework to improve our understanding and management of water cycle modifications in the Earth system